Microalgae cultivation strategies using cost–effective nutrient sources: Recent updates and progress towards biofuel production. (October 2022) - Ganesh Saratale, Rijuta; Ponnusamy, Vinoth Kumar; Jeyakumar, Rajesh Banu; Sirohi, Ranjna; Piechota, Grzegorz; Shobana, Sutha; Dharmaraja, Jeyaprakash; Lay, Chyi–How; Dattatraya Saratale, Ganesh; Seung Shin, Han; Ashokkumar, Veeramuthu
Graphical abstract: Highlights: Discussed intrinsic relation of algae cultivation strategies using inexpensive nutrient sources. Advancements in cultivation techniques for enhanced biomass production. Current status for microalgae biofuels at large-scale production. Addressed challenges and future prospectives Microalgal biorefinery as feasible approach. Abstract: Scientists are grabbing huge attention as well as consciousness on non–renewable energy sources for the global energy crises because of gradual increase in oil price, fast depletion or low availability of resources, and the release of more toxic–gases (CO2, SOx, Nx O) during exhaustion, etc . Due to such hitches, the key need is to find alternative biofuels or feedstocks to replace fossil fuel energy demands worldwide. Currently, microalgae have become intrigued feedstock candidates (3rd generation source of biofuel) to replace nearly 50–60 % of fossil fuels due to high production of biomass and oil, mitigating CO2 and wastewater remediation. The present work demonstrated the current developments and future perspectives on large–scale algal cultivation strategies for the biorefinery economy. In addition, various advanced cultivation techniques adopted for enhanced biomass production and cost-effective methods for bioenergy production were detailly discussed.